Phase transition in disordered ferroelectric ceramic Pb0.70 Ca0.30 Ti O3 under pressure - Chandra A.; Pandey D.; Tyagi A.K.; Mukherjee G.D.; Vijayakumar V. (My University, 2025)
Pressure dependent synchrotron x-ray diffraction studies on Pb0.70 Ca0.30 Ti O3 (PCT30) ferroelectric ceramic reveal a crossover in the nature of phase transition from first order nature observed at ambient pressures to second order at high pressures. It is shown that Ca2+ doping affects the transition temperature but does not change the transition pressure of PbTi O3 significantly. The values of bulk modulus and its pressure derivative are also given in this letter. © 2007 American Institute of Physics.